Metabolic Changes Induced by Deletion of Transcriptional Regulator GCR2 in Xylose-Fermenting Saccharomyces cerevisiae - Minhye Shin; Soo Rin Kim (Microorganisms, 2020)
Glucose repression has been extensively studied in Saccharomyces cerevisiae, including the regulatory systems responsible for efficient catabolism of glucose, the preferred carbon source. However, how these regulatory systems would alter central metabolism if new foreign pathways are introduced is unknown, and the regulatory networks between glycolysis and the pentose phosphate pathway, the two major pathways in central carbon metabolism, have not been systematically investigated. Here we disrupted gcr2, a key transcriptional regulator, in S. cerevisiae strain SR7 engineered to heterologously express the xylose-assimilating pathway, activating genes involved in glycolysis, and evaluated the global metabolic changes. gcr2 deletion reduced cellular growth in glucose but significantly increased growth when xylose was the sole carbon source. Global metabolite profiling revealed differential regulation of yeast metabolism in SR7-gcr2Δ, especially carbohydrate and nucleotide metabolism, depending on the carbon source. In glucose, the SR7-gcr2Δ mutant showed overall decreased abundance of metabolites, such as pyruvate and sedoheptulose-7-phosphate, associated with central carbon metabolism including glycolysis and the pentose phosphate pathway. However, SR7-gcr2Δ showed an increase in metabolites abundance (ribulose-5-phosphate, sedoheptulose-7-phosphate, and erythrose-4-phosphate) notably from the pentose phosphate pathway, as well as alteration in global metabolism when compared to SR7. These results provide insights into how the regulatory system GCR2 coordinates the transcription of glycolytic genes and associated metabolic pathways.